Next-generation Sequencing Revealed a Novel Mutation in the Gene Encoding the Beta Subunit of Rod Phosphodiesterase - Shen, Sherry (2014)
PURPOSE: To report the phenotypes caused by a novel mutation in the PDE6B gene in a family with two affected siblings and one affected cousin with a 2-year follow-up. DESIGN: Three patients from a family with a history of retinitis pigmentosa underwent clinical evaluations. The affected patients’ DNA was analyzed using next-generation sequencing and segregation analyses were performed for the family. SETTING: Edward S. Harkness Eye Institute, New York Presbyterian Hospital. PARTICIPANTS: Two siblings, one cousin, and five unaffected family members. MAIN OUTCOME MEASURES: Macular appearance assessed by funduscopy, autofluorescence imaging, spectral-domain optical coherence tomography and visual function assessed by electroretinography. RESULTS: The proband, brother, and cousin had rod-cone degeneration with cystoid macular edema. Fundus autofluorescence showed hyperautofluorescent ring constriction over time. Spectral-domain optical coherence tomography revealed retinal pigment epithelium atrophy, loss of external limiting membrane, retinal layer thinning, and reduction in ellipsoid zone length over time. Next-generation whole exome sequencing revealed a homozygous c.1923_1969ins6del47 nonsense PDE6B mutation, which has not been previously described, that segregated with the disease in the family. CONCLUSIONS: The homozygous PDE6B mutation causes retinitis pigmentosa. Acetazolamide treatment improved visual acuity but rod degeneration continued. Despite having the same mutation and living in the same environment, the proband’s brother progressed at a faster rate starting at a younger age, suggesting that gene modifiers may influence the expressivity of the phenotype. Next-generation sequencing, used to discover this mutation, is a practical new technology that can detect novel disease-causing alleles, where previous arrayed primer extension (APEX) technology could not.